Conservation and Adaptive Reuse of Maratha-Era Wadas in Maharashtra: Architectural, Cultural, and Socio-Historical Perspectives (International Journal of Food and Nutritional Sciences, 2025)
Maratha-era Wadas in Maharashtra are architecturally and culturally significant structures that embody the social, historical, and environmental heritage of the region. This study investigates the architectural features, socio-cultural relevance, and adaptive reuse potential of these heritage buildings to propose sustainable conservation strategies. A descriptive-exploratory methodology was adopted, combining archival research, field surveys of 15 representative Wadas across Pune, Satara, and Kolhapur, and semi-structured interviews with heritage experts and local residents. Findings indicate that 40% of the surveyed Wadas are in poor condition, 33% in moderate condition, and only 27% are well-preserved, highlighting the urgent need for restoration interventions. Architecturally, 87% of Wadas retained their original courtyard-centric layout, while 73% showed deterioration in timber elements and decorative features. According to Socio-cultural analysis, only 65 percent of the communities remember the historical significance of Wadas but these communities are not involved in proper activities. Another option is the adaptive reuse opportunities which are identified in 47%, 33 and 20 percent of Wadas that could become cultural centers, museums, or venue as a boutique hospitality or educational building. The study focuses on the importance of policy backing, community intervention, and wholesarmal planning to have sustainable conservation. These lessons can be used towards preserving the Maratha-era Wadas as heritage objects of living heritage, which can juxtepose historical preservation with modern functionality.